An ancient theory of interaction between fact and fiction in poetic texts and Zono de’ Magnalis’ accessus to the Aeneid (ENTHYMEMA, 2014)
One of the Greco-Roman theories of the relationship between fact and fiction in poetic texts remained quite widespread in the medieval commentary tradition. The unpublished accessus to the Aeneid by Zono de’ Magnalis (early 14th cent.) presents an unusual variant of this theory.
Keywords: Fiction; medieval scholarship; Zono de’ Magnalis; Vergil